Makanan Halal dan Thayyib Perspektif Mufassir Nusantara - Mausufi, Nurul; Hidayat, Muhammad; Fitriani, Fitriani (AHKAM, 2023)
The concept of halal and thayyib food, namely food that is permitted by shari'at, nutritious, safe (does not contain substances that are harmful to the body and mind and is past its expiry date or mixed with unclean objects), proportionate according to its content, delicious (food containing the taste is not disgusting for consumption) and clean. The purpose of this research is to find out the concept of halal food and thayyib from the perspective of Indonesian mufassir. This research is included in library research (Library Research), namely research conducted using literature (library) both in the form of Nusantara interpretation books such as the interpretation of An-Nur, Al-Azhar, and Al-Misbah, as well as books, theses or journals that study related to halal food and thayyib which are descriptive analysis. The results of this study indicate that the Mufassir Nusantara, namely Buya Hamka, M. Quraish Shihab, and M. Hasbi Ash-Shiddiqiey, interpret halal thayyib in a more specific and conditional way, that is, it is not just pure, not unclean, and does not harm the body, mind and mind. However, halal and thayyib food must be healthy food, have adequate and balanced nutrition, and be proportional (not excessive) according to the levels. The concept of thayyib in the view of mufassir Nusantara is in accordance with the General Pattern of Balanced Nutrition (PUSG) which can be a guideline in terms of consuming food today.